PROGRAM PELAKSANAAN SENAM AEROBIK SECARA BERKELANJUTAN YANG BERTUJUAN UNTUK PENINGKATAN KEBUGARAN DAN KUALITAS HIDUP PADA KELOMPOK LANSIA DI JATIRAHAYU KECAMATAN PONDOK MELATI KOTA BEKASI - RATU KAREL LINA; Yudhia Fratidhina; Ganesa Puput Dinda Kurniawan; Rovika Trioclarise (Jurnal Pengabdian Masyarakat Fisioterapi dan Kesehatan Indonesia, 2022)
This community service is carried out for community empowerment by making a program for implementing aerobic exercise in a sustainable manner which aims to increase fitness in the elderly group in Jatirahayu, Pondok Melati sub-district Bekasi City. The method used in this community service uses four schemes: assessment, problem formulation and planning, implementation, and evaluation, and in its performance, nine program activities are carried out. This activity concludes that the provision of a sustainable aerobic exercise program can improve fitness, improving the quality of life in the elderly group in Jatirahayu, Pondok Melati District, Bekasi City.